2014
DOI: 10.5539/ies.v7n8p23
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Usefulness and Ease of Use of the Learning Management System as a Learning Tool

Abstract: A Learning Management System (LMS) can be a singularly critical platform to report on students' learning progress and to monitor students' learning engagement. At the only defence university in Malaysia, the National Defence University of Malaysia (NDUM) adopts the LMS as a supplementary learning and teaching tool. Nonetheless, the aspiration of Malaysia to ensure that higher learning institutions actively participate in the Massive Open Online Course (MOOC) has further emphasised the need for the NDUM to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 10 publications
2
24
0
8
Order By: Relevance
“…En el caso de los alumnos de la Universidad de Córdoba, participantes en este estudio, se manifiestan abiertos a su empleo, por lo que es positiva su percepción de un desarrollo de su proceso de aprendizaje a través de las PTM, en este caso Moodle (Green, Inam y Denton, 2012;Maz, Barcho, Jimenez y Adamuz, 2012;Felpeto, Rey, Fernández-Vázquez y Garrote, 2015;Juhary, 2014;Srichanyachon, 2014), sin embargo, si atendemos al género, vemos que los hombres son los que más se decantan en su participación en este tipo de formación.…”
Section: Conclusionesunclassified
See 1 more Smart Citation
“…En el caso de los alumnos de la Universidad de Córdoba, participantes en este estudio, se manifiestan abiertos a su empleo, por lo que es positiva su percepción de un desarrollo de su proceso de aprendizaje a través de las PTM, en este caso Moodle (Green, Inam y Denton, 2012;Maz, Barcho, Jimenez y Adamuz, 2012;Felpeto, Rey, Fernández-Vázquez y Garrote, 2015;Juhary, 2014;Srichanyachon, 2014), sin embargo, si atendemos al género, vemos que los hombres son los que más se decantan en su participación en este tipo de formación.…”
Section: Conclusionesunclassified
“…En lo que se refiere a las ventajas de su empleo, consideran que tanto el fácil como el rápido acceso a la información, la claridad con que se muestran los contenidos y la estructura organizativa de la materia (Juhary, 2014;Eskandari y Soleimani, 2016;Wu y Hung, 2013) son aspectos destacables.…”
Section: Conclusionesunclassified
“…This flexibility is particularly important for those who want to continue their education while working part-or full-time. Studies have demonstrated that e-learning is welcomed by students when supported by a learning management system (e.g., Dang & Robertson, 2010;Juhary, 2014;Lonn & Teasley, 2009;Martín-Blas & Serrano-Fernández, 2009). Nguyen (2015) found that online learning is generally at least as effective as the traditional format.…”
Section: Introductionmentioning
confidence: 99%
“…As técnicas quantitativas de análise de dados empregadas pelos artigos foram: análise fatorial exploratória ou análise de componentes principais (Algers & Silva-Fletcher, 2015;Guo, Zhang, Bonk, & Li, 2015;Hu et al, 2015;Kursun, Cagiltay, & Can, 2014;Pirkkalainen, Jokinen, & Pawlowski, 2013;Pirkkalainen, Pawlowski, & Pappa, 2017;Ye, Recker, Walker, Leary, & Yuan, 2015); análise fatorial confirmatória ou modelagem de equações estruturais (baseadas em correlação ou em mínimos quadrados parciais) (Kelly, 2014;Mtebe & Raisamo, 2014a;Pirkkalainen et al, 2017;Zhou, 2016); regressão múltipla (Kim et al, 2015;Mtebe & Raisamo, 2014a;Pirkkalainen et al, 2013;Raman, Achuthan, Nedungadi, Diwakar, & Bose, 2014;Van Acker, Vermeulen, Kreijns, Lutgerink, & Van Buuren, 2014); técnicas descritivas e exploratórias como análise dos coeficientes de correlação (Hu et al, 2015;Juhary, 2014;Reed, 2012;Thoms & Thoms, 2014); comparações de médias utilizando testest, ANOVA e quiquadrado (Cohen et al, 2015;Delimont, Turtle, Bennett, Adhikari, & Lindshield, 2016;Fischer, Hilton, Robinson, & Wiley, 2015;Guo et al, 2015;Hassall & Lewis, 2017;Hilton III, Fischer, Wiley, & Williams, 2016;Hu et al, 2015;Jongsermtrakoon & Nasongkhla, 2015;Jung, Sasaki, & Latchem, 2016;Kimmons, 2015;Kurelovic, 2015;Li & Hu, 2013;A. Murphy, 2...…”
Section: Métodos Empregadosunclassified
“…O desafio da sustentabilidade financeira, de equilibrar fluxos de receitas (diante do conceito de abertura) com os fluxos de despesas, cria dependência de recursos governamentais (Stacey, 2013) e da filantropia (Valentino, 2015). Isso é um problema pois financiamento por projeto como prêmios, auxílio governamental não são sustentáveis no longo prazo: muitos projetos foram descontinuados com o fim dos fluxos de receitas desse tipo (Weibel et al, 2009 Abordagens comportamentais passam pela percepção (Delimont et al, 2016;, crenças (Deimann & Farrow, 2013;Van Acker et al, 2014), atitudes (Lindshield & Adhikari, 2013;Reed, 2012), aceitação (Juhary, 2014;Zhou, 2016), motivação (Beaven, 2013;Huang et al, 2012), engajamento (Huang et al, 2012), experiência (P. Murphy & Wolfenden, 2013;Nistal & Fonte, 2014) e satisfação (Adnan et al, 2017).…”
Section: áReas De Aplicação E Casosunclassified